ISLAMIC FINANCE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article explores the core principles of Islamic finance, its applications in modern economies, and the opportunities it provides for sustainable economic growth.It examines the challenges faced by the Islamic finance industry and proposes innovative approaches to overcome them. The study incorporates a review of key literature, analyses global trends, and presents actionable recommendations for fostering Islamic finance in diverse financial ecosystems.